2011
DOI: 10.1093/cvr/cvr209
|View full text |Cite
|
Sign up to set email alerts
|

Connexin 43 gene therapy prevents persistent atrial fibrillation in a porcine model

Abstract: Our results highlight the contribution of Cx43 to the pathophysiology of AF and demonstrate the viability of gene therapy for prevention of atrial arrhythmias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
111
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(118 citation statements)
references
References 37 publications
6
111
0
1
Order By: Relevance
“…Furthermore, the RA of the PAH dogs contained a higher level of unphosphorylated Cx43 and more heterogeneous Cx43 expression than the RA of the control dogs. Previous studies have demonstrated that heterogeneous Cx43 expression may enhance susceptibility to arrhythmia, 18,19 as it is associated with dispersed impulse conduction. Taken together, our findings suggest that regional changes and greater heterogeneity of Cx43 expression provide the substrate for AF/AFL vulnerability in PAH dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the RA of the PAH dogs contained a higher level of unphosphorylated Cx43 and more heterogeneous Cx43 expression than the RA of the control dogs. Previous studies have demonstrated that heterogeneous Cx43 expression may enhance susceptibility to arrhythmia, 18,19 as it is associated with dispersed impulse conduction. Taken together, our findings suggest that regional changes and greater heterogeneity of Cx43 expression provide the substrate for AF/AFL vulnerability in PAH dogs.…”
Section: Discussionmentioning
confidence: 99%
“…A recent paper showed that overexpression of connexin43 in atrial tissue prevents atrial fibrillation in the porcine burst-pacing model (36). Another group also performed gene transfer of connexins (connexin40 or connexin43) using a similar animal model (37).…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the results of our study, we could hypothesize that the stimuli we used may act differently on connexin expression, modulating Cx43 while Cx40 could be influenced by other conditions not tested in the present study. A recent study on animals suggest that downregulation of Cx43 is of major importance in determining myocardial susceptibility to AF development (Bikou et al 2011), although this finding needs further validation in humans.…”
Section: Myocardial Hypoxia/ischemia and Atrial Fibrillationmentioning
confidence: 97%